Pencapaian Maslahah Melalui Etika Bisnis Islam Studi Kasus Restoran Mie Akhirat - Dany Hidayat; Fatin Fadhilah Hasib (Universitas Airlangga, 2015)
This research aims to understand the implementation of business ethics within the restaurant “Mie Akhirat”. This Research uses a qualitative approach entailing a descriptive case study of the object and a purposive sampling technique. The data used are collected through a semistructured interview. Analysis of data is carried out by using the descriptive analysis model. The result of this research is expected to reveal the business ethics implemented within the restaurant. This research hopes to benefit by exposing examples of islamic business ethics implemented by the restaurant. This research suggests that the implementation of islamic business ethics would be of great benefit for the whole of society including their economiccondition.